1982
DOI: 10.1111/j.1528-1157.1982.tb05046.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intelligence Following Temporal Lobectomy: Relationship to EEG Activity, Seizure Relief, and Pathology

Abstract: Pre- and posttemporal lobectomy measures of intelligence and memory in 36 patients with medically refractory complex partial seizures were compared with (1) various aspects of presurgical ictal and interictal EEG activity derived from surface and deep electrodes, (2) postlobectomy seizure relief, and (3) pathological findings in the resected lobe. With respect to interictal EEG data, bilaterally synchronous surface spikes (accompanied or unaccompanied by simultaneous deep spikes) and sharp waves were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…As reported elsewhere (Crandall, 1973;Engel et al, 1981;Lieb et al, , 1982, the utilization of SEEG has been beneficial, with significant reduction in the seizure frequency of patients after surgical treatment. Data are presented on patients who participated in the UCLA depth-electrode program from 1974 to 1980.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…As reported elsewhere (Crandall, 1973;Engel et al, 1981;Lieb et al, , 1982, the utilization of SEEG has been beneficial, with significant reduction in the seizure frequency of patients after surgical treatment. Data are presented on patients who participated in the UCLA depth-electrode program from 1974 to 1980.…”
Section: Discussionmentioning
confidence: 70%
“…Also, neither the unsuccessful surgical patients nor the nonsurgical patients benefitted from repeated testing. In addition, a corresponding increase in social rating, as well as the tester's clinical judgement of improvement in the patients' general performance levels, adds validity to the interpretation of at least some real increase in intelligence for the seizure-relieved patients (Matarazzo et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…When the epileptic condition improves, many patients also experience impressive psychosocial improvements after operation (29). Complete freedom from complex partial seizures for at least 2 years or more can be expected for 40 to 70% of patients.…”
Section: Results Of Anterior Temporal Lobectomymentioning
confidence: 99%
“…Until recently, cognitive impairment was considered a strong contraindication for surgical intervention of epilepsy. Past research linked poor postoperative seizure control with low IQ (Chelune et al 1998;Duchowny 1989;Lieb et al 1982;Lieb et al 1980;Rausch and Crandall 1982); however, more recent studies have not found this to be the case (Khoury et al 2005;Levisohn 2000). Davies et al (2009) note that many of these early surgical procedures were conducted prior to the dawn of MRI, which is now used to identify patients with generalized, widespread epileptogenicity prior to surgery for exclusion purposes.…”
Section: Surgerymentioning
confidence: 99%